A Conceptual Architecture and a Framework for Dealing with Variability in Mulsemedia Systems - Saleme, Estêvão Bissoli; Santos, Celso Alberto Saibel; Ghinea, George (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2020)
The thesis is within the emerging topic of mulsemedia systems, which encompass audiovisual content associated with multisensory effects, users' quality of experience, and human-computer interaction. It presents a conceptual architecture and a framework that take into account the challenges and requirements for mulsemedia delivery systems identified from the gaps and shortcomings in related work. Furthermore, the work's outcome brings multiple and valuable contributions relying on a complex and solid experimental setup, which have been shared and published in relevant journals and conferences.